EVALUACIÓN DE LA CARTERA DE CRÉDITO DE LA COOPERATIVA DE AHORRO Y CRÉDITO “EDUCADORES DE LOJA LTDA” DE LA CIUDAD DE LOJA, EN EL PERIODO 2014-2015.PROPUESTA DE MEJORAMIENTO - Jaramillo Tigre, Krupskaya Ivannova (2017)
The present thesis work called "EVALUATION OF THE CREDIT PORTFOLIO OF THE COOPERATIVE OF SAVINGS AND CREDIT" EDUCADORES DE LOJA LTDA. "OF THE CITY OF SHOP, IN THE PERIOD 2014-2015. PROPOSAL FOR IMPROVEMENT. "Its main objective is to carry out the evaluation of the Loan Portfolio, the same that was prepared with the purpose of knowing the economic and financial situation of the entity through the application of financial indicators, which are the Represented graphically with their respective percentages and interpretation with the purpose of presenting results. In compliance with the main objective, financial indicators of delinquency, coverage of portfolio provisions and productive assets / liabilities with cost were applied, which allowed to determine that the cooperative has a high percentage of delinquency of the Consumer Credit Portfolio in the year 2015 with 47.27% surpassing the goals established by the institution. Subsequently, it establishes the levels of delinquency considering the parameters established by the Superintendency of Popular and Solidarity Economy for the execution of the same and in this way to be able to make the comparison against The results obtained after applying the respective indicators of the study subjects years. That is why, in the face of this situation, the respective report was prepared and a proposal for improvement framed in the appropriate Recovery of Portfolio, which will allow the credit area to identify and designate the responsibilities and functions of the credit staff , Also based on the results obtained, the conclusions 5 are presented with their respective recommendations, which indicate that an evaluation has not been made to the credit portfolio, harming the cooperative because, by ignoring the behavior of the portfolio, it can not take measures Corrective measures, negatively influencing the recovery of these, impairing their liquidity and solvency